TaWRKY13-A Serves as a Mediator of Jasmonic Acid-Related Leaf Senescence by Modulating Jasmonic Acid Biosynthesis - Qiao, Hualiang; Liu, Yongwei; Cheng, Lingling; Gu, Xuelin; Yin, Pengcheng; Li, Ke; Zhou, Shuo; Wang, Geng; Zhou, Chunjiang (Frontiers in Plant Science, 2021)
Leaf senescence is crucial for crop yield and quality. Transcriptional regulation is a key step for integrating various senescence-related signals into the nucleus. However, few regulators of senescence implicating transcriptional events have been functional characterized in wheat. Based on our RNA-seq data, we identified a WRKY transcription factor, TaWRKY13-A, that predominately expresses at senescent stages. By using virus-induced gene silencing (VIGS) method, we manifested impaired transcription of TaWRKY13-A leading to a delayed leaf senescence phenotype in wheat. Moreover, overexpression (OE) of TaWRKY13-A accelerated the onset of leaf senescence under both natural growth condition and darkness in Brachypodium distachyon and Arabidopsis thaliana. Further, by physiological and molecular investigations, we verified that TaWRKY13-A participates in the regulation of leaf senescence via jasmonic acid (JA) pathway. Expression of JA biosynthesis genes, including AtLOX6, were altered in TaWRKY13-A-overexpressing Arabidopsis. We also demonstrated that TaWRKY13-A can interact with the promoter of AtLOX6 and TaLOX6 by using electrophoretic mobility shift assay (EMSA) and luciferase reporter system. Consistently, we detected the higher JA level in TaWRKY13-A-overexpressing lines than that in Col-0. Moreover, our data suggested that TaWRKY13-A is partially functional conserved with AtWRKY53 in age-dependent leaf senescence. Collectively, our study manifested TaWRKY13-A as a positive regulator of JA-related leaf senescence, which could be a new clue for molecular breeding in wheat.